Study of Bacteriological Profile and Antibiotic Sensitivity of Neonatal Sepsis in a Tertiary Care Hospital - Alam, Didarul; Islam, Shanjana; Roy, Tarun Kumar; Rahman, Mahmudur; Shahid, Md; Sharmin, Shahanaj (Journal of Chittagong Medical College Teachers' Association, 2018)
Background: Neonatal sepsis is a major cause of mortality and morbidity in newborn. The spectrum of organisms causing sepsis is different in developing countries. Data on the recent trends of organisms causing sepsis are limited. There are many factors that contribute to neonatal sepsis. The organisms responsible for early and late onset sepsis are different. This study was conducted to analyze the organisms responsible for early and late onset neonatal sepsis and to see the sensitivity of drugs. Materials and methods: A prospective hospital based study over the period of one year (January 2015 to December 2015) was conducted at Neonatal Intensive Care Unit (NICU) in Bangabandhu Memorial Hospital, USTC, Chittagong. Results: A total of 114 neonates were enrolled during the study period. Among them 98 neonates were selected considering inclusion and exclusion criteria. Blood culture was positive in 44(44.9%) neonates. The male female ratio of culture proven sepsis was 1.2:1. More than half were preterm 24(54.54%) LBW 27(61.37%). Among all of the culture-proven septic neonates, Klebsiella 22 (64.7%) were found to be the most common organism in early onset sepsis. Escherichia coli 6(60%) was common in late onset sepsis. Other organisms causing sepsis were Pseudomonas 10(22.72%) and Staphylococcus areus 2(4.54%) among all culture proven sepsis. We observed high resistance to penicillin against all organisms. Ceftazidime had good sensitivity against Pseudomonas. Quinolones and Aminoglycosides were sensitive mostly against Klebsiella, then Pseudomonas and E. coli. Imipenam showed good sensitivity against Klebsiella. Conclusion: Klebsiella were the most common organism in early onset sepsis. Escherichia coli was significantly more common in late onset sepsis than early onset sepsis. Resistance to penicillin and cephalosporin are increasing day by day. Our study revealed that quinolones and imipenam had good sensitivity against most of the organism in neonatal sepsis. JCMCTA 2017 ; 28 (2) : 53-58